Rekomendasi Kelayakan Penerima Kredit Menggunakan Metode TOPSIS dengan Pembobotan ROC - Sholihaningtias, Dian Nur (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2023)
The process of applying for credit (loan funds) by customers is one of the many forms of service at the Bank. To approve credit applications, the bank, especially the credit manager, must carry out a complex assessment in accordance with the standard requirements that apply to the bank, this is due to minimizing the risk of bad credit because customers cannot make installment payments in the future. Due to the complexity of the considerations in determining the eligibility of customers who apply for credit, limited employees (labor) and also the evaluation process that is still done manually so it takes a long time, so to overcome these problems, we need a system that can provide recommendations for customer decisions that are acceptable. in applying for credit using a decision support system method, one of which is used in this study is the Technique For Others Reference by Similarity to Ideal Solution (TOPSIS) method with the weighting Rank Order Centroid (ROC) method. The criteria used in this appraisal process include the price of the vehicle, down payment (DP), income, customer character and housing status. Based on the calculation results according to predetermined criteria, the highest value is 0,86 and the lowest value is 0,10.